SEKOLAHKU BUKAN MARATUAKU Pendidikan Agama Di Daerah Terdepan, Terluar, dan Tertinggal. Studi Kasus Pulau Maratua Kabupaten Berau Provinsi Kalimantan Timur - Baso Marannu (EDUCANDUM, 2018)
The theme of the study conducted in Berau District, East Kalimantan, Casestudy the primary school in Maratua Sub-district was "Implementation ofReligious Education in the 3T area (Leading, Outermost and Remote) ". Thisstudy used a qualitative method by field research approach focusing onprimary schools in four villages, namely SD Teluk Harapan, SD Teluk Alulu,SD Payung-Payung and SD Bohe Silian. The results of this study conclude ingeneral that research, there are four things that will support teachercompetencies in learning that are holistic and integrative in teacherperformance, including (a) religious teachers must know students in depth,especially the character and background of their parents in religious educationand religion in the family; (b) Religious Teachers are expected to master boththe disciplinary content and teaching materials in the school curriculum (c)The religious teacher must carry out with full responsibility the implementationof educational learning which includes the planning and implementation oflearning, process evaluation and learning outcomes, as well as follow-up forrepairs and enrichment; and (d) sustainable development of personality andprofessionalism. Teachers who have competence will be able to carry out theirduties professionally. This study recommends the Ministry of Religion asfollows: To the Ministry of Religion of Berau District it is possible to providethe widest possible opportunity for religious teachers on Maratua Island to beable to continue their education from a diploma to an undergraduate degree,especially lectures for special areas (3T). The need for support from the BerauDistrict government to improve school facilities and infrastructure, the oldbuildings must be renewed immediately by building new classes, especiallyschools whose buildings are made of Ulin wood such as SDN in Payungumbrellaand in Alulu Bay, including the intensity of school supervisors inMaratua District . To support Religious Education in Basic Education in BerauDistrict, Maratua District, religious activities by the community shouldcontinue to be intensified, so that children also feel and familiar with religiousactivities in Maratua District